Type-C RNA Virus Gene Expression in Human Tissue - Strand, Mette (1974)
Partially purified fractions of human tissues have been analyzed by competition radioimmunoassay for the presence of two of the principle structural components of type-C RNA viruses, the major core protein (p27 to p30) and the major envelope glycopeptides (gp69/71). Screening of tissues was carried out by use of a heterologous assay system of (125)I-labeled Rauscher murine virus p30 antigen and anti-RD 114 virus serum which was found to detect a class of interspecies determinants common to murine, feline, and primate viruses. A competitor with the same apparent affinity for antibody binding as that of purified viral core proteins was found in relatively high concentration in tissues from patients with systemic lupus erythematosus, in some neoplastic tissues, and also in normal human tissues. This competitor from a lupus spleen chromatographed on phosphocellulose and showed size fractionation during gel filtration similar to known p27 to p30 viral proteins. An immunologically reactive protein was also demonstrated by immunodiffusion and by immunoprecipitation of (125)I-labeled human protein with anti-RD 114 p28 serum. Analysis of these human competitor proteins with homologous assay systems of viral core proteins and corresponding antisera showed that all, including the normal tissue extracts, appear similar to core proteins of known viruses, especially the RD 114 and woolly monkey species. A hypothesis suggested by these data is that many, if not all, humans harbor at least part of the genome of one or more type-C viruses, the properties of which are similar to those of viruses from other mammalian species, particularly primates.